Psychoeducation Programs to Reduce Preoperative Anxiety in Adults: A Scoping Review - Oliveira, Palmira; Porfírio, Catarina; Pires, Regina; Silva, Rosa; Carvalho, José Carlos; Costa, Tiago; Sequeira, Carlos (MDPI, 2023)
Abstract: Background: Surgical procedure is a critical event that causes anxiety for patients. One of the possible intervention strategies to reduce anxiety in the preoperative period is psychoeducation. Methods: A scoping review was conducted according to the JBI methodology and PRISMA-ScR to map knowledge about psychoeducation programs to reduce preoperative anxiety in adults. The data were extracted by the researchers, according to the objective of the study. Finally, the data synthesis was presented in narrative format and tables. Results: four studies were included in the review with different characteristics of psychoeducation programs. The approach of these programs consisted of teaching about anxiety, instruction and training in anxiety control techniques. The contents referred to included the surgical process and intervention techniques to reduce anxiety. Program sessions lasted from 45 to 150 min, with a frequency of 1 to 6. The assessment instrument used was the State- Trait Anxiety Inventory. The dynamisers were nurses, psychotherapists and clinical psychologists. Conclusions: Psychoeducation programs can be useful and effective in reducing anxiety. More studies are needed to confirm these results
Keywords: Adult; Preoperative anxiety; Psychoeducation; Nursing; Scoping review